2021
DOI: 10.1017/gmh.2021.2
|View full text |Cite
|
Sign up to set email alerts
|

Two-year treatment effects of the common elements treatment approach (CETA) for reducing intimate partner violence and unhealthy alcohol use in Zambia

Abstract: Background Intimate partner violence (IPV) and unhealthy alcohol use are common yet often unaddressed public health problems in low- and middle-income countries. In a randomized trial, we found that the common elements treatment approach (CETA), a multi-problem, flexible, transdiagnostic intervention, was effective in reducing IPV and unhealthy alcohol use among couples in Zambia at a 12-month post-baseline assessment. In this follow-up study, we investigated whether treatment effects were sustained among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…Men’s voluntary participation in couple-based programmes reflects a desire to improve their relationship functioning. A RCT in Zambia compared counselling sessions separately for men and their spouses to no treatment (Kane et al , 2021; Murray et al , 2020; Murray et al , 2021). Couples ( n = 123) were randomised into the combined programme finding men’s alcohol use and IPV perpetration significantly reduced after treatment completion (Murray et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Men’s voluntary participation in couple-based programmes reflects a desire to improve their relationship functioning. A RCT in Zambia compared counselling sessions separately for men and their spouses to no treatment (Kane et al , 2021; Murray et al , 2020; Murray et al , 2021). Couples ( n = 123) were randomised into the combined programme finding men’s alcohol use and IPV perpetration significantly reduced after treatment completion (Murray et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Couples (n = 123) were randomised into the combined programme finding men's alcohol use and IPV perpetration significantly reduced after treatment completion (Murray et al, 2021). Follow-up at 24 months postbaseline showed no significant changes in AOD or IPV outcomes with authors suggesting that treatment gains were sustained for two years (Kane et al, 2021). A sub-set of couples reported that skills learnt in the programme included strategies to avoid conflict, anger management, reduce alcohol use and improved empathy for their partner (Murray et al, 2021).…”
Section: Factors To Enhance Engagementmentioning
confidence: 99%
“…The trial was ended early based on recommendation of the data and safety monitoring board due to an interim data analysis indicating a clear benefit of CETA at 12 months; participants in the control arm were then offered CETA [ 37 ]. Study investigators followed the original CETA participants for an additional 12 months for a 24-month post-baseline assessment [ 42 ]. Family members, including adolescents, in the CETA arm completed Consumer mhIST following their 12-month post-baseline assessment.…”
Section: Methodsmentioning
confidence: 99%
“…De la misma manera, Bauch et al (2022) encontraron que la negligencia infantil y el estrés de los padres disminuyó significativamente después de su participación en un programa de terapia multisistémica. Con respecto a intervenciones dirigidas a hombres perpetradores de violencia íntima de pareja, Kane et al (2021) evaluaron la eficacia a mediano plazo del tratamiento de elementos comunes (CETA), intervención flexible y multiproblemática, donde se consideran las particularidades de los participantes, y las diferentes problemáticas que presentan. Los autores evidenciaron que el tratamiento de elementos comunes (CETA) fue un tratamiento eficaz para reducir la violencia de pareja y el consumo nocivo de alcohol, resultados que se mantuvieron durante al menos dos años desde el comienzo de la intervención.…”
Section: Diagnóstico Recibido En La Adultez En Hombres Perpetradores ...unclassified